LEGAL CERTAINTY OF VILLAGE ASSET LAND USED FOR SCHOOL BUILDINGS: A REVIEW OF MINISTER OF HOME AFFAIRS REGULATION NO. 3/2024 - Fauzan, Muhammad; Haspada, Deni; Asril, Juli (Universitas Labuhanbatu, 2025)
Village asset land has a vital role as a supporter of development and a source of village income, but there are often issues of legal certainty over its ownership and management status, especially when utilized as a school building. Therefore, a clear regulation and settlement mechanism in accordance with laws and regulations are needed so that village assets remain protected and can be optimally utilized for the public interest. This research aims to analyze the legal certainty of land ownership of village assets used as school buildings based on the Regulation of the Minister of Home Affairs Number 3 of 2024. The method used is normative juridical with a descriptive-analytical approach through the review of legislation, legal doctrine, and relevant secondary data. The results show that village land used for schools remains legally classified as village assets and must be managed in accordance with the principles of transparency, accountability, and legal certainty. The land exchange mechanism—as regulated in Articles 25 and 48A of Minister of Home Affairs Regulation No. 3 of 2024—requires replacement with land of equal or higher value, and proper certification under the village government's name. However, its implementation faces challenges, including uncertified land ownership, limited legal capacity of village officials, and bureaucratic hurdles in administrative approval, all of which hinder effective and lawful asset management and the preservation of the land’s social function. Keywords: Village assets; legal certainty; school; certification; swap